Analisis Peran Komunikasi Dalam Membentuk Citra Organisasi Islam Dalam Era Media Sosial - Dina Rosiyana; Mila Setyaningrum; Ismail Ismail (PT. ALHAFI BERKAH INDONESIA, 2023)
Commuication is an important part of organization. one of them is islamic organization. An islamic organization is a group or community that is bound. Internal communication is very important to interact with the public in order to provide trust to the public so that people can invite to cooperate or bussiness collaboration. Communication strategies, such as the use of media, public relations to contribute to the growth of islamic organizations. Social media can make a positive contribution to islamic organization by increasing situational awareness and willingness to learn. Organization like Muhammadiyah can use social media to educate their follwers. Social media can also improve their ability to respond to crises and motivate social media users to become better.